Shifting Trend of Multinational Corporations : Old Versus New - Farahdiba Bachtiar (WANUA : Jurnal Hubungan Internasional, 2015)
MultinationalCorporation(MNC)isnotanewtopicinInternationalPolitical EconomyeitherinInternational Relationsstudy.Asithadbeenoperatingallovertheworldasmuchashavingappearedinmanypapersandresearch. However,thereisashiftingtrend,atleastsinceadecadeagoregardingtherise of  MNC from Emerging  Countries. Surprisingly,  the North  –Southrelationswhichhadbeenwellestablishfacedre-formulated tobecomeSouth- SouthevenSouth–Northrelations.Thefirmsfromdevelopingeconomies are comingintoglobalmarkets andchangingtheshapeoftradecompetition, investmentandregulation.BythepresenceofMNCfromemergingcountries theeconomicarchitectureasawholeandinternational tradeasapartofit fundamentallychanged.